Asymptomatic bacteriuria among pregnant women - Kerure, Sudha Biradar; Surpur, Rajeshwari; Sagarad, Sheela S.; Hegadi, Sneha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Urinary tract infections (UTIs) are the most common bacterial infections during pregnancy. Asymptomatic bacteriuria (ASB) is a major risk factor for the development of urinary tract infections during pregnancy and with further risk of preterm birth & pyelonephritis if untreated. Aims & Objectives: This study was carried out to determine the prevalence of asymptomatic bacteriuria (ASB) in pregnant women & to isolate, identify and establish antimicrobial susceptibility of pathogens. Methods: A total of 500 pregnant women were studied over a period of one year. Clean catch midstream urine sample was collected into a sterile container & then subjected to culture method. Results: Significant bacteriuria was noted in 45 patients (9%). 3% patients had insignificant bacteriuria. Growth of contaminants was noted in 8%. 80% samples were sterile with no growth. E. coli was the most common etiological agent, followed by Staphylococcus aureus. Conclusions: Asymptomatic bacteriuria is not uncommon in antenatal patients. All pregnant women should be screened by urine culture to detect asymptomatic bacteriuria at their first visit to prevent overt UTI & other complications in both mother & fetus.